Characterizing Distress and Identifying Modifiable Intervention Targets for Family Caregivers of Patients with Malignant Gliomas - Forst, Deborah A; Kaslow-Zieve, Emilia R; Hansen, Andrea; Mesa, Michelle; Landay, Sophia L; Quain, Kit M; Sereno, Isabella; El-Jawahri, Areej; Greer, Joseph A; Temel, Jennifer S; Jacobs, Jamie M (Journal of palliative medicine, 2023)
Individuals caring for patients with malignant gliomas experience high rates of anxiety; however, an in-depth understanding of their distress and evidence-based interventions to target their needs are lacking. We conducted semistructured interviews with caregivers with elevated anxiety to characterize their drivers of anxiety, identify modifiable intervention targets, and capture their preferences for a psychosocial intervention. From 9/2017 to 3/2019, we conducted semistructured interviews with 21 caregivers of patients with malignant gliomas, at time points following the patient's diagnosis or within one to three months after the patient's death. Eligible caregivers in the United States had clinically significant anxiety as measured by a Hospital Anxiety and Depression Scale-Anxiety score >7. Three independent coders employed thematic content analysis to analyze the qualitative data with NVivo 12, achieving high intercoder agreement (Kappa = 0.98). On average, caregivers were 54.81 years old ( 10.85) with elevated anxiety ( 10.90, 3.25). We identified six themes in which caregivers described (1) coping through reassurance seeking or avoidance, (2) changes in their relationship with the patient, (3) challenges with social support, (4) vacillation between certainty and uncertainty regarding the future, (5) devaluation of self-care for the patients' needs, and (6) challenges communicating with the health care team. Caregivers were interested in an intervention soon after the patient's diagnosis, yet expressed concern about finding the time to participate. Emergent themes characterized the distress experienced by caregivers of patients with malignant gliomas and provided insight into their psychosocial intervention preferences. We identified evidence-based intervention components based on the modifiable factors arising from these themes.